ANALISIS KESESUAIAN LAHAN AGROFORESTRI BERBASIS SISTEM INFORMASI GEOGRAFI (SIG) DI DESA SINDULANG KABUPATEN SUMEDANG - Widodo, Prasetyo; Susila, Rian (Wanamukti: Jurnal Penelitian Kehutanan, 2018)
The condition of social, economic, and culture of forest community has effect to forest condition. Desa Sindulang is one of village that community forest in Taman Buru Masigit Karembi that has majority of farmer and low economic condition. But commodity planting is carried out without an evaluation of the land to determine the level of suitability of the land with the commodities planted. The method by overlay Land Mapping Unit with society land use then analyze of matching suitability land. The results of evaluation divided in 3 units, are : 1) unit I which have land suitability class values with forestry commodities such as Suren (Toona sureni) and Coffee (Coffea Arabica) while agricultural commodities such as Broccoli (Brassica oleracea), Chili (Capsicum annum), Banana (Musa acuminate) and Cabbage (Brasica oleracea). 2) Units II which have land suitability class values with forestry commodities such as Suren (Toona sureni) and Coffee (Coffea arabica) while agricultural commodities such as Tomato (Solanum lycopersicum). 3) Units III which have land suitability class values with forestry commodities such as Suren (Toona sureni), Africa (Maesopsis eminii) and Coffee (Coffea arabica) while agricultural commodities such as Tomato (Solanum lycopersicum), Eggplant (Solanum melongena) Broccoli (Brassica oleracea), Chili (Capsicum annum), Cabbage (Brasica oleracea) and Pineapple (Ananas Comosus).Keywords : Agroforestry, Land suitability, Sindulang Village